Estudo de arco elétrico em subestações de um sistema industrial - PINHEIRO JUNIOR, Valberto Costa (2018)
The goal of this work is to calculate the incident energy incoming from arc-flash and propose the proper level of vestment of protection, looking for the reduction of the hazards caused by this incidents in instalations of an industrial unity with isolated system of electrical generation. Because it’s extremely dangerous to the safety of the workers that Interact with the electric system, from the arc-flash, it has to be measured in conformity with the existent rules and the riscs must be controlled and mitigated, in the manner to not compromise the fisical integrity of the people and installation. In this way, the present study is justified, because in accordance with the IEEE 1584 it has to be realized the arc-flash study to determine properly the personal protective equipment necessary once that if it’s used the personal protective equipment superdimensioned, beyond the desconfort caused. News riscs will be created for the workers.